Functional engineering of microneedles for transdermal drug delivery - Chew, Sharon Wan Ting (Nanyang Technological University, 2021)
Microneedles (MNs) have emerged as a promising platform for effective transdermal drug delivery because of its non-invasiveness, ease of application, and ability to ensure controlled and targeted drug delivery. However, there is a lack of solutions to resolve several shortcomings related to applications of MN (potential bacterial infection and skin irritation) and its inability as a drug delivery platform to deliver living therapeutics. Two strategies were proposed to address these shortcomings – surface engineering strategy and materials engineering strategy. Surface engineering of MN platform using coating methods was utilized to confer additional functionality to the MN platform. Hydrothermal method was employed to incorporate antibacterial coating on MN, achieving antibacterial functionality. To improve on the fixation issue, nonaqueous dendrimer bioadhesive was coated on the surface of the MN to improve the adhesive strength of the MN platform and allow for hydrophobic drug loading. Next, materials engineering strategy was utilized to achieve effective transdermal cell delivery with MN platform. Cryomicroneedles (cryoMNs) which was conceived from the integration of cryopreservation concept with MN platform was proposed for the loading of cells and spheroids. CryoMNs demonstrate great potential as a platform for cell therapy and tissue regeneration applications.